Classroom Management Strategies for Improving the Effectiveness of History Instruction in Grade 11A at SMAN 1 Sindue Tobata, Donggala Regency - Miszartin Miszartin; Misnah Misnah; Mahfud M. Gamar; Minarni Nongtji (Journal of Educational Sciences, 2026)
Schools play a strategic role in developing students’ potential through effective and conducive learning processes. Effective classroom management contributes to increased student engagement, discipline, and learning effectiveness. This study aims to analyze classroom management strategies in enhancing the effectiveness of history learning in Class XI A at SMAN 1 Sindue Tobata. The background of this study is based on the continued presence of various obstacles in the learning process, such as low student attention and participation, disruptive behavior, and an unproductive classroom environment. The study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the study indicate that the main challenges include students’ lack of discipline, varying learning abilities, and an uncomfortable physical classroom environment. To address these challenges, the teacher implemented classroom management strategies through the enforcement of discipline based on class agreements, the use of varied teaching methods such as discussions and question-and-answer sessions, and the management of the physical classroom environment, including seating arrangements, cleanliness, lighting, and ventilation. These strategies proved effective in increasing student activity, concentration, and engagement in learning. Thus, effective classroom management plays a crucial role in creating a conducive learning environment and supports the optimal achievement of history learning objectives.